Respuesta :

Hello.

The anser is: -4

Step 1: Simplify both sides of the equation.

3(x+4)−x=4

(3)(x)+(3)(4)+−x=4(Distribute)

3x+12+−x=4

(3x+−x)+(12)=4(Combine Like Terms)

2x+12=4

2x+12=4

Step 2: Subtract 12 from both sides.

2x+12−12=4−12

2x=−8

Step 3: Divide both sides by 2.

2x/2=−8/2

=-4

have a nide day


Hey there

the answer is

3(x+4)−x=4

3(x+4)−x=4

(3)(x)+(3)(4)+−x=4

3x+12+−x=4

(3x+−x)+(12)=4

2x+12=4

2x+12−12=4−12

2x=−8

x=−4

thank you

best regards

          OFFICIALLYSAVAGE2003